Risk-Based Compliance Management : Making it Work in Border Management Agencies - World Bank (Washington, DC, 2014)
The World Bank's publication Border Management Modernization (2011) provides policymakers and reformers with a comprehensive 'whole of government' perspective on improving trade facilitation through better border management. This reference and implementation guide has been developed to supplement the information provided in the World Bank publication. Specifically, it builds on the contents of chapter six (Core border management disciplines: risk-based compliance management) and chapter eleven (Reform instruments, tools, and best practice approaches) by providing: an introduction to the key issues associated with the practical implementation of a modern risk-based compliance management regime in border management agencies; a step-by-step method of establishing a compliance management approach in a border management agency; practical examples covering a range of border management activities to illustrate the methodology; and useful tips to help identify and rationalize or eliminate resource intensive, time consuming and ineffective regulatory processes. Proper border management is critical to the cost effectiveness of international trade transactions and the smooth flow of legitimate goods and people from the perspective of both the public and private sectors. Risk management is at the heart of border management efficiency and effectiveness and is the key to achieving the balanced approach. The most important consideration from a risk management perspective is to ensure that the relevant risk has been properly identified, to avoid the possibility of introducing extraneous variables into the subsequent risk management decision making process.